Model Of The Entrepreneurial Process For Early Childhood: Model Of The Entrepreneurial Process For Early Childhood - Rahman, afif; Mardiah; Anshari, Muhammad Fatih (UMBanjarmasin, 2022)
In a developing country, the role of entrepreneurs cannot be ignored, especially in carrying out development. A nation will develop faster if it has entrepreneurs who can be creative and innovate optimally, namely realizing new ideas into real activities in every business. This method use the method used is the library method. by taking study materials from various reference sourcescitations